EXPLORATION OF ADOLESCENTS' KNOWLEDGE ABOUT SALT WATER SOAK HYDROTHERAPY FOR SCABIES PATIENTS AT DAR EL HIKMAH ISLAMIC BOARDING SCHOOL, PEKANBARU. - Rini Hariani Ratih (LPPM Universitas Abdurrab, 2026)
Background: Scabies is a contagious skin disease that is still often found in Islamic boarding schools due to overcrowding, lack of personal hygiene, and low knowledge about disease prevention and management. One non-pharmacological effort that can be used to help improve the comfort of scabies sufferers is salt water immersion hydrotherapy. Objective: To explore adolescents' knowledge about salt water immersion hydrotherapy in scabies sufferers at Dar El Hikmah Islamic Boarding School, Pekanbaru. Method: This study used a qualitative method with an exploratory descriptive approach. Participants were selected using a purposive sampling technique by considering certain criteria relevant to the research objectives. Data collection was carried out through in-depth interviews using semi-structured interview guidelines. Data were analyzed using thematic analysis through the stages of data reduction, data presentation, and drawing conclusions to obtain the main themes. Results: The results of the study showed that most adolescents were aware of scabies as a contagious skin disease, but their knowledge about salt water immersion hydrotherapy was still varied. Some participants understood that saltwater soaks can help reduce itching and provide comfort, while others obtained information solely from family, friends, or personal experience without understanding the benefits and proper application method. Furthermore, health education and access to information were found to be factors influencing adolescents' knowledge of saltwater hydrotherapy. Conclusion: Adolescents' knowledge of saltwater hydrotherapy for scabies sufferers varies and is influenced by their experience and the source of information they receive. Appropriate and ongoing health education is needed to improve adolescents' understanding of the use of saltwater hydrotherapy as a complementary therapy to improve the comfort of scabies sufferers in Islamic boarding schools. Keywords: adolescent knowledge, saltwater hydrotherapy, scabies, Islamic boarding schools, qualitative research.